Exploring the Radicalization Process in Young Women. Issue 7 (2nd October 2020) - Morgades-Bamba, Clara Isabel; Raynal, Patrick; Chabrol, Henri
ABSTRACT: Women's radicalization is a pending issue in empirical research that is worthy of attention. It has been found that the role of women in international terrorism is much greater than previously thought, but we know almost nothing about the factors underlying the process that would lead them to perpetrate radicalized acts, as almost no empirical research has been carried out on the subject. In this work we aim to explore a model of radicalization of thought and action among young women. The hypothesized model included ten predictors: cultural identity, cultural discrimination, religious involvement, depressive symptoms, and schizotypal, borderline, and the Dark Tetrad traits of personality. Dogmatism was hypothesized as a mediator between these factors and the level of radicalized cognitions and behaviors. The sample comprises 643 college women (aged 18 to 29) from French universities. Our results suggest that women becoming involved in radicalization are more "dark" than "disturbed." Schizotypal, borderline, and depressive features, although being associated to radicalization, do not contribute to the model. Both the dark traits and socio-cultural factors are revealed as predictors of radicalization, while dogmatism is clearly shown as a mediator. Orientations in terms of prevention among young women are proposed.